Toxicity of Essential Oils of Origanum vulgare, Salvia rosmarinus, and Salvia officinalis Against Aculops lycopersici - Thomas Giordano; Giuliano Cerasa; Ilaria Marotta; Mauro Conte; Santo Orlando; Adele Salamone; Michele Massimo Mammano; Carlo Greco; Haralabos Tsolakis (Plants)
The tomato russet mite (TRM), Aculops lycopersici, is a destructive pest of tomato crops worldwide. It poses a significant challenge to growers in both greenhouse and open-field conditions. Traditional chemical control methods are often ineffective, promote resistance, and have negative environmental impacts. This has prompted the search for alternative strategies, such as biological control and eco-friendly botanical pesticides. In this study, we evaluated the acaricidal effects of essential oils (EOs) extracted from three officinal plants, Origanum vulgare L., Salvia rosmarinus Spenn., and Salvia officinalis L., cultivated using precision aromatic crop (PAC) techniques. Their efficacy was evaluated against A. lycopersici under laboratory conditions. The chemical composition of the EOs was determined by solid-phase microextraction (SPME) coupled with gas chromatography–mass spectrometry (GC-MS). The dominant component of O. vulgare EO was carvacrol (83.42%), followed by ρ-cymene (3.06%), and γ-terpinene (2.93%). In S. rosmarinus, α-pinene (28.0%), 1,8-cineole (11.00%), and borneol (7.72%) were the major components. S. officinalis EO was characterized by high levels of 1,8-cineole (27.67%), camphor (21.91%), and crisantenone (12.87%). We tested multiple concentrations (320–5000 μL L−1) and exposure times (1–4 days) to assess mite mortality. The results revealed both dose- and time-dependent toxic activity, with significant differences among EOs. O. vulgare EO was the most toxic, causing 90% mortality at 0.5% (w/v) concentration after 4 days. S. rosmatinus and S. officinalis EOs had more limited effects, with 46% and 42% mortality, respectively. Lethal concentration (LC50) values were 2.23 mL L−1 (95% CI: 1.74–3.05) for O. vulgare, 5.84 mL L−1 (95% CI: 3.28–22.29) for S. rosmarinus, and 6.01 mL L−1 (95% CI: 2.63–261.60) for S. officinalis. These results indicate that O. vulgare EO shows efficacy comparable to commercially available botanical pesticides. Our findings support the potential of O. vulgare EO as a viable alternative for the control of A. lycopersici, contributing to integrated pest management (IPM) strategies.